Post‐pancreatitis diabetes mellitus is common in chronic pancreatitis and is associated with adverse outcomes. Issue 1 (1st December 2022) - Dugic, Ana; Hagström, Hannes; Dahlman, Ingrid; Rutkowski, Wiktor; Daou, Diana; Kulinski, Paula; Löhr, J.‐Matthias; Vujasinovic, Miroslav
Abstract: Background: Post‐pancreatitis diabetes mellitus (PPDM) is a common consequence of chronic pancreatitis (CP). We aimed to determine the incidence and predictors of PPDM after CP onset, as well as complications and antidiabetic therapy requirements, in a high‐volume tertiary center. Methods: We did a cohort study with retrospectively collected data from patients with definite CP seen at the Karolinska University Hospital between January 1999 and December 2020. Cause‐specific Cox regression analysis was used to assess PPDM predictors. To estimate risk of complications and need for therapy the Fine‐Gray subdistribution hazard model was employed, accounting for death as a competing risk. Results: We identified 481 patients with CP. The cumulative incidence of PPDM was 5.1%, 13.2%, 27.5% and 38.9% at 5, 10, 15 and 20 years, respectively. Compared to CP patients without diabetes, patients with PPDM were predominantly male (55% vs. 75%), had more frequently alcoholic etiology (44% vs. 62%) and previous acute pancreatitis. The only independent predictor of PPDM was presence of pancreatic calcifications (aHR = 2.45, 95% CI 1.30–4.63). Patients with PPDM had higher rates of microangiopathy (aSHR = 1.59, 95% CI 1.02–2.52) and infection (aSHR = 4.53, 95% CI 2.60–9.09) compared to CP patients who had type 2 diabetes (T2DM). The rate of insulin use was three‐fold higher, whereas metformin use rate was two‐fold higher in the same comparison. Conclusions: Patients with PPDM have a higher frequency of clinically significant complications and were more commonly prescribed insulin and metformin, suggesting a more aggressive phenotype than that of T2DM. Greater PPDM awareness is needed to optimize disease management. Abstract :